Position measurements at GNSS station SMR5 in 2024 with links to TRIMBLE binary data files - Andrés F Zakrajsek; Ralf Krocker (PANGAEA, 2025)
SMR5 GNSS long-term raw-data series is aimed at contributing to the scientific research of Earth-System-involved global- as well as Antarctic-regional processes, improving International Terrestrial Reference Frame (ITRF) redefinitions, and benefiting society through enhanced GNSS-derived applications and services. The dataset was gathered at the Argentinean (Antarctic) research station San Martín in the year 2024. Approximate position in ITRF2014 frame at epoch 2024.5: X=927077.27m, Y=-2195043.59m, Z=-5896521.08m or in (GRS80) ellipsoidal coordinates: lat=68°07 extquotesingle46.850S, lon=067°06 extquotesingle11.598W, h=26.8m, orthometric height above EGM2008 geoid amounts 17.3m. GNSS receiver: TRIMBLE NetR9 (SN: 5226K50357), GNSS antenna: Zephyr Geodetic 2 w/Dome, PN: 57971-00 (SN: 30976593), Sampling interval: 1 second. Each file covers a time period of one day. Original binary files are of TRIMBLE proprietary format T02. The files of one day have been combined applying UNIX tool tar.
In: Schenke, Hans Werner; Zakrajsek, Andrés F; Vey, Sibylle; Krocker, Ralf (2012): Position measurements at GPS station SMR5 [dataset publication series]. Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research, Bremerhaven, PANGAEA, https://doi.org/10.1594/PANGAEA.770301